Analisa Penerapan Manajemen Operasional Pada Perusahaan Manufaktur PT. Sri Indah Aluminium Extrusion Di Kota Batam - Fendy Cuandra; Cecilia Cecilia; Jasen Jasen; Jenny Jenny; Loius Loius; Yen Diarti (STIE AMKOP, 2023)
Operational management is a major management function in a manufacturing company which is usually used to be a strategic tool to compete with other companies. Operation management is needed to create a new innovations and changes for the better. The company provides good product quality but does not forget he environmental impact of all the company’s production activities. PT. Sri Indah Aluminium Extrusion was established in 2003, in Batam City. PT. SIAE is one of the manufacturing companies in Batam City which is engaged in Aluminium. PT.SIAE PT. Sri Indah Aluminum Extrusion is a company engaged in aluminum smelting, die-casting and extrusion. This company was founded by Stefanus Yusup in 2003 in the city of Batam, which is located on Jalan Engku Putri, Tunas Industrial Estate Block 1 E. This company has a total of 40 employees Keywords: Operation Management, Manufacture Company, Production